Hubungan Kontrol Diri Dengan Perilaku Cyberloafing Pada Personil Polri Polda Sumatera Barat - HADI, MUHAMMAD HADI PERMANA; Mario Pratama (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
The presence of the convenience of technology and the internet actually aims to provide convenience for those who need to maintain rhythm and consistency in carrying out their work. The behavior of using the internet for matters that are not for work purposes or personal use is known as cyberloafing behavior. This act of Cyberloafing has a negative influence which results in impacts such as reducing employee fertility, a low sense of compliance and discipline, breaching confidentiality, the Company's credibility fading, and increasing internet financing. The type of research used in this research is quantitative research. The subjects used in this research were police officers from the West Sumatra Regional Police. The proportional sampling technique is the choice for sampling. This research uses two scales, namely the cyberloafing behavior scale and the self-control scale. The data analysis method used in this research is simple linear regression analysis. The research results show a correlation coefficient value of -0.157 and a p value of 0.008. From the research results, it can be concluded that there is a significant negative relationship between Cyberloafing Behavior and Self-Control in West Sumatra Regional Police Personnel.